2020
DOI: 10.1177/0218492320971492
|View full text |Cite
|
Sign up to set email alerts
|

Video-thoracoscopic left cardiac sympathetic denervation for long-QT syndrome

Abstract: Background Congenital long-QT syndrome represents the most common cardiac channelopathy and manifests as potentially lethal ventricular arrhythmias. Prevention strategies include beta-blockade pharmacotherapy, implantable cardioverter-defibrillators, and left cardiac sympathetic denervation, which can increase the threshold for ventricular fibrillation. Herein, we report our experience with video-assisted thoracoscopic left cardiac sympathetic denervation. Methods We performed a retrospective review of the ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
(18 reference statements)
0
2
0
1
Order By: Relevance
“…[42] Besides, video-assisted thoracoscopic left cardiac sympathetic denervation (VATS-LCSD) is a less invasive surgical procedure [Figure 2B], without serious complications, including Horner syndrome. [43] A previous study demonstrated that VATS-LCSD is a low-morbidity procedure that achieves a marked response in Chinese LQTS patients [Figure 2C and D]. [44] Gene-specific therapies LQT2 patients are extremely sensitive to serum potassium levels, which should be maintained at an appropriate level.…”
Section: Lifestyle Modificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[42] Besides, video-assisted thoracoscopic left cardiac sympathetic denervation (VATS-LCSD) is a less invasive surgical procedure [Figure 2B], without serious complications, including Horner syndrome. [43] A previous study demonstrated that VATS-LCSD is a low-morbidity procedure that achieves a marked response in Chinese LQTS patients [Figure 2C and D]. [44] Gene-specific therapies LQT2 patients are extremely sensitive to serum potassium levels, which should be maintained at an appropriate level.…”
Section: Lifestyle Modificationsmentioning
confidence: 99%
“…In a research of 147 LQTS patients, there was a >90% reduction in cardiac events post denervation [42] . Besides, video-assisted thoracoscopic left cardiac sympathetic denervation (VATS-LCSD) is a less invasive surgical procedure [Figure 2B], without serious complications, including Horner syndrome [43] . A previous study demonstrated that VATS-LCSD is a low-morbidity procedure that achieves a marked response in Chinese LQTS patients [Figure 2C and D] [44] …”
Section: Therapymentioning
confidence: 99%
“…Esta técnica implica el aislamiento de los primeros tres o cuatro ganglios torácicos, preservando la porción cefálica del ganglio estrellado, para evitar el síndrome de Horner. Las limitaciones son logísticas, ya que su aplicabilidad depende de la experiencia del grupo quirúrgico, cuyo acceso puede ser por toracotomía o por toracoscopía 67 , 68 . En niños pequeños, el acceso es por el tercer espacio intercostal, donde hay una visualización adecuada del ganglio simpático y estrellado.…”
Section: Manejo Y Tratamientounclassified